ANALISIS KEMISKINAN DAN PENDAPATAN KELUARGA NELAYAN KASUS DI KECAMATAN WEDUNG KABUPATEN DEMAK, JAWA TENGAH, INDONESIA - Agunggunanto, Edy Yusuf (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
The poverty of fishermen has become a critical and complex issue. The level of fishermen’s povertyand income inequality are related to fishermen characteristic such as demographic, socio-economic, and socioculturalfactors. The objective of this study is to analyze the poverty an income inequality of fishermen, andfactors that influence it. The result of study shows fishermen experience and number of family influenceincome fishermen.